2018
DOI: 10.1038/s41598-018-31778-8
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomallei-loaded cells act as a Trojan horse to invade the brain during endotoxemia

Abstract: Neurologic melioidosis occurs in both human and animals; however, the mechanism by which the pathogen Burkholderia pseudomallei invades the central nervous system (CNS) remains unclear. B. pseudomallei-loaded Ly6C cells have been suggested as a putative portal; however, during melioidosis, lipopolysaccharide (LPS) can drive disruption of the blood-brain barrier (BBB). This study aims to test whether the Trojan horse-like mechanism occurs during endotoxemia. The expression levels of cerebral cytokines, chemokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Burkholderia can cause severe inflammation in immunocompromised individuals [ 41 ] and produce kynurenine and quinolinate [ 42 ], which are proinflammatory metabolites associated with symptom severity in PD [ 43 ]. Burkholderia has also been reported to infect the brain [ 44 , 45 ]. Of particular interest, Burkholderia species encode the rate-limiting enzyme for secondary bile acid synthesis (bile-acid dehydratase) [ 46 ], highlighting the fact that the appendix microbiome of PD sufferers has an enrichment of microbiota that metabolize bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderia can cause severe inflammation in immunocompromised individuals [ 41 ] and produce kynurenine and quinolinate [ 42 ], which are proinflammatory metabolites associated with symptom severity in PD [ 43 ]. Burkholderia has also been reported to infect the brain [ 44 , 45 ]. Of particular interest, Burkholderia species encode the rate-limiting enzyme for secondary bile acid synthesis (bile-acid dehydratase) [ 46 ], highlighting the fact that the appendix microbiome of PD sufferers has an enrichment of microbiota that metabolize bile acids.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies employed animal models to investigate how B. pseudomallei causes CNS infection. Previously, a monocyte (CD11b+) was found to act as a Trojan horse carrying B. pseudomallei across the cerebral endothelium and inducing neurological melioidosis in BALB/c mice [12,20]. Other studies in BALB/C and C75B1/6 mice demonstrated that B. pseudomallei cause CNS infection by invading the olfactory nerve or trigeminal nerve [10] and crossing the blood-brain barrier [9,33].…”
Section: Discussionmentioning
confidence: 99%
“…Microglial activation results in their production of proinflammatory cytokines such as interleukin 1 (IL-1), interleukin 6 (IL-6), interleukin 8 (IL-8), and tumor necrosis factor alpha (TNF-α) [19]. During murine melioidosis, the activation and expansion of microglia have been found in the brain [20]. However, the role of microglia against B. pseudomallei infection is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…According to Gendrin et al, GBS strains enhance their intracellular survival and propagation by abandoning their capsule. This mechanism does not involve concealment within macrophages (also called the “Trojan horse” mechanism 121 , 122 ). Concurrently, there is an observed increase in the permeability of the BBB associated with GBS 123 .…”
Section: Niche Adaptationmentioning
confidence: 99%